The effect of disinfectant agents in eliminating the contamination of dental unit water - (:unkn) unknown (WILEY, 2003)
High concentrations of water-borne organisms cause multiple public health problems. Contamination of water exiting the dental unit water lines could be inhibited with the use of some disinfectants. The purpose of this investigation was to establish the effect of two disinfectants and to test their capacity to eliminate colony forming units (CFU) per mL. Vacuum lines of four chairs were treated for a total of 2 weeks. Two disinfectants (Bio(R) 2000 and Alpron(R)) were used as per manufacturer's instructions. Water samples for hetereothrophic counts from each unit's air/water syringe line were collected before treating the first patient of the day. Baseline, daily, first and second week samples of 10 mL were plated on blood agar plates and eosin ethylene blue agar. For meosifilic bacterial counts, Mueller Hinton agar plates with 1 mL direct and 1/10 were used in sterile serum and CFU were counted. The suspected colonies were further evaluated using API 20E and API 20NE. No Gram(-) opportunistic pathogens were found during the entire observation. Baseline contamination level (>102 CFU mL(-1)) without use of disinfectants was significantly higher (P < 0.0001) than at both first and second weeks when disinfectants were used. No colony was formed when Bio 2000 was used after both first and second weeks, whereas small number of CFU mL(-1) was found at the end of the first week when Alpron (<10) was used. In conclusion, when used daily, both disinfectants prevent the development of bacterial contamination after first and second weeks with no significant differences (P = 0.35).
Keywords: dental unit water; disinfectants; biofilm; MICROBIAL-CONTAMINATION; BACTERIAL-CONTAMINATION; BIOFILMS